The measurement of state engagement in actions beyond basic professional duties - Agnieszka Bożek; Diana Malinowska (Nofer Institute of Occupational Medicine, 2020)
Background The goal of this paper is to present the phenomenon of engagement in actions that go beyond basic professional duties, and the factor structure and other psychometric properties of the daily measurements of this construct, which corresponds with the growing interest of researchers in the phenomenon of employee engagement, extra-role behaviors and the factors that affect them on a daily basis. Material and Methods The research was carried out among 62 full-time or part-time working students of the humanities and social sciences (79% of whom were female), using a 5-day on-line daily survey. The main measure was a modified Polish version of the 9-item questionnaire consistent with the Utrecht Work Engagement Scale (UWES), which was prepared on the basis of the adaptation of the State Work Engagement (SWE) questionnaire proposed by Breevaart et al. (2012) to measure daily work engagement. Results The obtained results have shown that the adapted version of the SWE questionnaire is a reliable and valid measure which can be used to measure daily fluctuations in beyond-duties engagement. The 3-factor multilevel model has a satisfactory fit. Conclusions The study contributes to the current body of literature by examining state engagement in actions that go beyond basic professional duties and the validity of its measurement. It also shows that giving employees more autonomy and feedback may positively influence their beyond-duties engagement. Med Pr. 2020;71(2):127-36